DAYA TARIK FESTIVAL DANGKONG DI KABUPATEN KARIMUN PROVINSIKEPULAUAN RIAU - Noviana, Rahmatul; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Dangkong Festival is known as Dangkong Dance Festival held in Karimun Regency is about routine cultural festival and part of Karimun Regency's anniversary celebrations, this festival is an art performance and attended by various regions, especially Serumpun Melayu. This study aims to (1) find out the various attractions in the Dangkong Festival in Karimun District, and (2) find out the efforts to improve Dangkong Festival as a tourist attraction that attracts tourists. The method used in this research is qualitative descriptive. The subjects of this study were key informants, namely Tourism and Culture Department of Karimun Regency, Sri Mayang Studio, and additional informants from the Moro Malay Customary Institute. The results of this study indicate that Dangkong Festival fulfills the criteria of tourist attraction that has the uniqueness, beauty, and values obtained in the festival. Dangkong Festival aims to promote various works of dance creation, preserve and introduce the tradition â€œJoget Dangkongâ€ which is a tradition of the Karimun community, and establish friendships between Malay nations. Until now, the government continues to make efforts to improve the existence of Dangkong Festival in the midst of the Karimun community, and can attract more tourists to visit Karimun district.Keywords: Attractions, Culture, Dangkong Festival